The Euro's Effecton Trade Imbalances - Berger, Helge (IMF Working Papers; Working Paper ;, 2010)
When does trade become a one-way relationship? We study bilateral trade balances for a sample of 18 European countries over the period from 1948 through 2008. We find that, with the introduction of the euro, trade imbalances among euro area members widened considerably, even after allowing for permanent asymmetries in trade competitiveness within pairs of countries or in the overall trade competitiveness of individual countries. This is consistent with indications that pair-wise trade tends to be more balanced when nominal exchange rates are flexible. Intra-euro area imbalances also seem to have become more persistent with the introduction of the euro, some of which is linked to labor market inflexibility. Reviewing the direction of imbalances, we find that bilateral trade surpluses are decreasing in the real exchange rate, decreasing in growth differentials, and increasing in the relative volatility of national business cycles. Finally, countries with relatively higher fiscal deficits and less flexible labor and product markets exhibit systematically lower trade surpluses than others.